2016
DOI: 10.1007/978-3-319-38963-9_1
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Humor

Abstract: Laughter and its close cousin, humor, are unique and important mammalian responses that may have evolved to strengthen social bonds and thereby enhance survival. For human infants, laughter and humor appear in the first six months of life and reveal their sensitivity to social and emotional cues, and their cognitive radar for incongruity. Understanding why infants engage in humorous interactions not only teaches us about infants, but about also about human experience in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…There is considerable evidence that awareness of others' intentions, expectations, and beliefs emerges as early as 7 months of age (Hamlin et al, 2007;Kovács et al, 2010). Clowning, teasing, and other "communicative games" in infancy and early childhood may require understanding of the minds of others (as argued by Mireault & Reddy, 2016), even if the incongruous acts themselves are not understood in a deep way (Airenti, 2016;Bergen, 1998;Bergen, 2019). In line with social interactionist theories of development, humor during play may, therefore, act as a "melting pot," providing a context for rehearsing existing social understanding skills and in turn, drive development and new competencies (Gibson et al, 2020;Lillard et al, 2013).…”
Section: Connections Between Humor Play and Social Understandingmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable evidence that awareness of others' intentions, expectations, and beliefs emerges as early as 7 months of age (Hamlin et al, 2007;Kovács et al, 2010). Clowning, teasing, and other "communicative games" in infancy and early childhood may require understanding of the minds of others (as argued by Mireault & Reddy, 2016), even if the incongruous acts themselves are not understood in a deep way (Airenti, 2016;Bergen, 1998;Bergen, 2019). In line with social interactionist theories of development, humor during play may, therefore, act as a "melting pot," providing a context for rehearsing existing social understanding skills and in turn, drive development and new competencies (Gibson et al, 2020;Lillard et al, 2013).…”
Section: Connections Between Humor Play and Social Understandingmentioning
confidence: 99%
“…Furthermore, the methods used for coding humor in this study may have been less sensitive to gender differences. Given that humor and laughter are related, but not synonymous (Mireault & Reddy, 2016;Singer, 2019), it is quite possible that our coding of humor within episodes that contained laughter-with the view to examine humor that was cued as playful and nonthreateningunderestimated boys' humor production (i.e., by not capturing humorous bids that did not generate amusement from their siblings). Some evidence suggests that by middle childhood, boys become more frequent jokers (McGhee, 1979;Paine, Howe, et al, 2019) and adopt more aggressive styles of humor (James & Fox, 2018), while girls produce more laughter in response to other people's humorous acts (McGhee, 1979).…”
Section: Gender and Gender Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, humor or funny information can facilitate liking and closeness in interpersonal relations (Cann and Matson, 2014;Treger et al, 2013). A sense of humor enables people to socially connect with others (Mireault and Reddy, 2016;Wisse and Rietzschel, 2014). Humor is also thought to contribute to sexual attraction (Mireault and Reddy, 2016;Wilbur and Campbell, 2011).…”
Section: Stimulus-organism-response Theorymentioning
confidence: 99%
“…A sense of humor enables people to socially connect with others (Mireault and Reddy, 2016;Wisse and Rietzschel, 2014). Humor is also thought to contribute to sexual attraction (Mireault and Reddy, 2016;Wilbur and Campbell, 2011). Cann and Matson (2014) also found that different humor styles are related to social desirability or undesirability.…”
Section: Stimulus-organism-response Theorymentioning
confidence: 99%